1947
DOI: 10.1037/h0060470
|View full text |Cite
|
Sign up to set email alerts
|

The Shipley-Hartford Retreat Scale as a measure of intellectual impairment for military prisoners.

Abstract: The MTOUSA * Disciplinary Training Center is the largest overseas installation for the confinement of American prisoners who were adjudged guilty, by a General Courts Martial, of violating one or more of the Articles of War. As part of the psychological evaluation of all prisoners at the institution, a routine testing program was instituted. 2 The testing battery included: 1. The Qualification Test as used in induction stations for literacy; 2. The Shipley-Hartford Test for intelligence and mental deteriorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1948
1948
1967
1967

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Wright [10] reports that N. P. patients show impairment on this scale, but no check on validity is offered. More recently, Manson and Grayson [4] report a high incidence of impairment in army prisoners as measured by the Shipley-Hartford Scale and believe the vocabulary score is too high. They recommend using other test scores against which the abstraction score can be compared.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…Wright [10] reports that N. P. patients show impairment on this scale, but no check on validity is offered. More recently, Manson and Grayson [4] report a high incidence of impairment in army prisoners as measured by the Shipley-Hartford Scale and believe the vocabulary score is too high. They recommend using other test scores against which the abstraction score can be compared.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…This difference of eight points proved to be not significant at the .05 level of confidence, which would suggest either that these brain-injured 5s were not experiencing a loss in conceptual thinking ability, or that this scale is actually not sensitive to such deficits. In view of the negative findings of previous experiments (1,6), the latter possibility is not unlikely.…”
Section: Resultsmentioning
confidence: 79%
“…bL Thus, if the norms for eighteen-yearolds are used, the normal person of 50 will apparently have suffered a vast amount of deterioration." I t has been demonstrated that this in fact is the case with the SHY and that the existing norms cannot be used with older age groups (Garfield & Fey, 1948;Lewinson, 1963;Manson & Grayson, 1947). The purpose of this study was to establish the parameters of "normal" performance on the SH "abstraction" tasks in relation to chronological age and vocabulary level.…”
mentioning
confidence: 97%